2009
DOI: 10.1002/cbic.200900060
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis of Peptide Dendrimers

Abstract: The ability of proteins and peptides to undergo proteolysis is essential to their biological function. Herein, we report the first detailed study of the protease reactivity of peptide dendrimers. Dendrimers are regularly ramified, tree-like synthetic macromolecules with promising application in technology and medicine. Using trypsin and alpha-chymotrypsin cleavage sites as models, we show that the protease reactivity of peptide dendrimers can be controlled by the degree of branching. Dendrimers with two or thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 57 publications
0
27
0
Order By: Relevance
“…We recently showed that peptide dendrimers of up to 40 residues that contain multiple short mono‐, di‐, or tripeptide branches can be efficiently prepared by solid‐phase peptide synthesis (SPPS) and display a range of biomimetic functions 8. Their dendritic topology induces a flexible yet relatively compact molten globule conformation9 resulting in good resistance to proteolysis 10. Considering that glycosylated versions showed useful lectin inhibition and anti‐biofilm activities against P. aeruginosa ,11 we asked the question whether a systematic survey of amino acid sequences within this multi‐branched topology might lead to peptide dendrimers with direct AMP‐like antimicrobial effects.…”
Section: Synthesis and Bioactivity Of Antimicrobial Peptide Dendrimermentioning
confidence: 99%
“…We recently showed that peptide dendrimers of up to 40 residues that contain multiple short mono‐, di‐, or tripeptide branches can be efficiently prepared by solid‐phase peptide synthesis (SPPS) and display a range of biomimetic functions 8. Their dendritic topology induces a flexible yet relatively compact molten globule conformation9 resulting in good resistance to proteolysis 10. Considering that glycosylated versions showed useful lectin inhibition and anti‐biofilm activities against P. aeruginosa ,11 we asked the question whether a systematic survey of amino acid sequences within this multi‐branched topology might lead to peptide dendrimers with direct AMP‐like antimicrobial effects.…”
Section: Synthesis and Bioactivity Of Antimicrobial Peptide Dendrimermentioning
confidence: 99%
“…In our efforts to explore this class of protein analogues, we have shown that screening of combinatorial libraries leads to peptide dendrimers with various functions, [4] such as catalysis of ester hydrolysis [5] and aldol reactions, [6] drug delivery, [7] biofilm inhibition mediated by lectin binding, [8] and programmed proteolysis. [9] We recently reported the identification of dendrimer B1 (Table 1) as a simple model for cobalamin transport proteins by screening of a peptide-dendrimer combinatorial library and structural optimization. [10] Dendrimer B1 binds cobalamin by coordination to cobalt through the thiolate of a cysteine residue at the dendrimer core.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Their dendritic topology induces a flexible yet relatively compact molten globule conformation [9] resulting in good resistance to proteolysis. [10] Considering that glycosylated versions showed useful lectin inhibition and anti-biofilm activities against P. aeruginosa, [11] we asked the question whether a systematic survey of amino acid sequences within this multi-branched topology might lead to peptide dendrimers with direct AMP-like antimicrobial effects.Initial combinatorial experiments identified bH1, with the sequence L 8 (BL) 4 (BF) 2 BK (B = branching 2,3-diaminopropanoic acid, Dap), as a simple, relatively small AMPD with only one residue per branch whose positive charges were provided by the eight amino termini. [12] This dendrimer showed significant activity against P. aeruginosa presumably by membrane disruption; [12,13] however, sequence variations were ineffective in improving its activity.…”
mentioning
confidence: 99%
“…[8] Their dendritic topology induces a flexible yet relatively compact molten globule conformation [9] resulting in good resistance to proteolysis. [10] Considering that glycosylated versions showed useful lectin inhibition and anti-biofilm activities against P. aeruginosa, [11] we asked the question whether a systematic survey of amino acid sequences within this multi-branched topology might lead to peptide dendrimers with direct AMP-like antimicrobial effects.…”
mentioning
confidence: 99%